ORGANIZATIONAL CULTURE, DISCIPLINE AND WORK MOTIVATION TO ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) EMPLOYEES - Fauzan Muttaqien (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2021)
Organizational citizenship behavior is an extra and voluntary individual behavior out of their duties and very effectiveness to support of the goals organization. The research aims to determine effect of organizational culture, discipline and motivation to OCB employees of PT. BPR Nur Semesta Indah, Jember Regency. The sampling method using saturated sampling technique with a sample size of 84 employees (Central and Branch). The analysis method used is multiple linear regression. The outcome analysis of the data explained that variables of organizational culture, discipline and motivation have significant influences on organizational citizenship behavior partially. And Simultaneously, organizational culture, discipline and motivation variables have significant effect on organizational citizenship behavior. The result of coefficient determination test shows that the variables of organizational culture, discipline and motivation have an effect of 84.9% on organizational citizenship behavior. And 15.1% remaining has influenced other variables which is not explained in thisreseach, such as style of leadership, organizational commitment and so on.